INTERPRETASI SURAT AL-BAQARAH AYAT 232 DAN PENGARUHNYA TERHADAP WEWENANG WANITA DALAM PERKAWINAN - Yustiloviani, Yustiloviani (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
Al-Baqarah: 232 describes the marriage of a woman who had finished her waiting period in order not to be prevented from marrying. There are two interpretations of this verse. First: This verse is a reprimand or an order addressed to the trustee not to preclude the woman remarry her ex-husband. Second, it is a reprimand or a command addressed to ex-husband not to hinder his ex-wife marrying a man she loves. Both of them affect marriage law. The effect of the first interpretation is an adult woman who will get married must get permission from the guardian and is vowed by him. The guardian has prerogative rigths of woman under his guardianship. In the wedding – vow procession women is passive. Meanwhile the impact of the second interpretation is that women have the right to determine her future husband even can perform her wedding vow herself without depending on the guardian. The guardian in this procession is not required at all, marriage is not based on guardian authority but based on the consent of women. The interpretation of Al-Baqarah:232 is more accurately assumed that adult women have the authority to determine the preferred candidate husband. In the vow implementation, women should authorize to the guardian or trustee for her benefit and for her rights protection.